Flora Sinensis Michała Boyma SI - Miazek, Monika (Wydawnictwo Fundacji Collegium Europaeum Gnesnense, 2005)
“Michał Boym was lucky with researchers. Although it often grieves us that he is forgotten by his followers, it was written more about him than about any of the six Polish Jesuits working in the Far East in the Xvii and XVIIIc.” – writes Duc Ha Nguyen. In fact the last two centuries have brought many monographic articles and four books dedicated to the person and the work of Michał Boym (1612–1659), a Polish Jesuit who because of his research deeds is an important scholar in the European sinology. Also wrote about him his brethren from the Society of Jesus (eg.: J. de la Sérvier, E. Malatesta, J. Krzyszkowski), and also secular researchers – scientists researching various aspects of his research (e.g.: R. Chabrié, P. Pelliot, B. Szczęśniak, E. Kajdański). The bibliography of works mentioning Michał Boym – mostly swiftly mentioned, sometimes yet as a crucial element – contains a couple hundred items8. Among them are trials to depict the whole life and work of the Polish Jesuit, and also works devoted to small parts of it (e.g.: the Venetian episode of Boym’s stay in Europe, his cartographic works or his attitude to the writings of Marco Polo). The variety of the publications subjects, as well as their scientific importance, is comparable to Michał Boym’s diversity of works and the intensity of his life. Regardless of the subject of a publication, almost all of them, similarly to every biographical note in the dictionaries or encyclopaedias, the name Boym is accopmanied with a title Flora Sinensis. This natural connection of the author and his most famous work does not mean that this work has been fully and completely analysed. Published in 1656 in Vienna Flora Sinensis was the first in Europe systematic description of the Far East Flora. The earlier partial, sometimes completely fictional information about that world of flora could only be found in ancient works, starting from Herodot, and the next centuries and great expeditions to the East (e.g. the expedition of Alexander the Great in IVc. BC, Marco Polo trips in XIIIc.) systemetically enlarged the knowledge. In XVII often in the travel dairies of missionaries and tradesmen exotic plants and animals were mentioned, but always they were only observations made by non-professionals off their geographic, ethnology and trade observations. Michał Boym as the first European tried to systemise the plants of the Far East, creating it the issue of his work. His composition gave the XVIIc. Europe a systematic, wide knowledge about fauna and flora of the Far East, which were presented from two perspectives: the first criteria of the selection was unusual character, oddity of the described plants and animals, the second one – their usefulness (almost every description contains information on the economic or medicinal values). Boym does not present the full picture (the size of Flora is not big enough, the work contains only 71 pages), but presents certain items of the Far East flora and fauna – the most interesting ones. In this manner, presenting almost pars pro toto, depicts the whole picture of an exotic world of fauna and flora and it literary speaking depicts, as the text is accompanied with woodcut pictures, which in some specimen were hand painted using water paints. At the moment of the publishing Flora Sinensis reached a wide interest in the scientific milieu of Europe, and was quickly translated into French and was partly published in monographs devoted to China and in compilations dealing with the Far East. It was then the prime information source for all eager to gain knowledge about still yet misterious China. The XXc. changed the perspective and in the studies of his contemporaries Flora Sinensis became one of the items to learn about the history of nature sciences in Europe. The researchers of the XXc. (as S. Krzemieniewski, B. Namysłowski, E. Kajdański, J. Zabłocki, H. Walravens) present its modernity in contrast with the knowledge of the time on the nature of the Far East, the correctness of the given data, author’s competence. Regardless of the change in the function of the work which occurred with time, Boym’s work has always been treated as a botanic writing (it was put aside – not without a cause – even the zoological issues) and in this context was analysed more or less carefully, while with a more careful analysis this text bears much wider selection of topics and issues. Flora Sinensis is an interdisciplinary piece of work, and researching it requires joining the competence of different scientific fields, as on its pages research fields from classical philology, sinology, history of the missions and botanic join. Presenting the many threads of Boym’s work, I shall reveal that we can perceive Flora Sinensis simultaneously as a botanic and zoological work, medical, missiological, political, sinological and also as a literary piece. It shall be done with the presentation of a wide historic and political background, which had a great influence on the final shape of Flora Sinensis, and also a detailed theoretical and literary analysis of particular parts of the work, with a particular focus on the role of the introductory part, almost completely discarded from the research. A particular attention shall be focused on scientific talks of the work, pointing to a specific construction of Flora Sinensis and poetry reserved for scientific papers. It seems that the problem of the talks in Latin scientific writings has not been properly analysed yet. As a basic tool for the analysis I used rhetoric theory – worked out in the ancient times, which became more detailed and transferred according to the Baroque taste. The treatment of rhetoric not only as a research subject but also as a key to interpreting works, was already established among the researchers of literature in Poland and other countries. H. Lausberg used as a subtitle in his monumental work Literary rhetoric a statement “The basics of literature knowledge”, and presenting the aim of his work in the preface he wrote that it is to help philologists dealing with the practical interpretation of texts”. Because in Poland in XVII c. the influence of rhetoric, which was a basis for the whole system of Jesuit’s schooling system, was on every work overwhelming, thus more correct it seems to make the rhetoric theory a tool for a better understanding of a form and the content of this baroque piece of work as is Flora Sinensis. The rules of invention and elocution which Michał Boym acquired with his education in the Jesus Society’s colleges became thus a basis for the construction of the work and its ordering power. The presentation of the origins of Boym’s work and the analysis and interpretation of its contents, and also its meaning in the history of European science is a vast introduction to the editing of the text of Flora Sinensis. Despite its particular importance in the author’s country Flora Sinensis has not been critically published or translated into Polish. And there was not a re-edition of the text, which was worked out by western researchers (e.g. extracts of Boym’s work were translated into German by H. Walravens17, who later published a wide – yet still not complete – translation along with an introduction in a digitalised form on a CD). Such negligence seems to be more severe as Boym’s work not only confirms the membership of XVIIc. Polish literature to the circles of European Latinitas, but also widens its interest range. Thus proves that the scientific and research impulse from the central and east Europe enriched the common European heritage19. It is worth remembering in the context of contemporary integration of our continent, when we search for people and models confirming Poland’s membership within the European family. To fill in the gap, in the second part of this publication I placed a transcription of the Flora Sinensis text with a translation to Polish and a commentary. The text of the transcription might be compared to photocopies of the original, enclosed with this book on a CD. The basis for the edition is a copy of Flora Sinensis from the Kórnik Library collection (sign. 412), which photocopies were available to me by courtesy of Stanisław Sierpowski, the manager of the library, whom I would like to show my gratitude. The worth of this issue is in giving the researchers the Latin text of Flora Sinensis, the original of which was difficult to reach. It may become a basis for future research on Latin in Baroque, with its peculiar syntax, orthography, punctuation and vocabulary and also on the scientific discourse within the XVIIc. works. Pointing attention to the form and poetry of scientific works at the beginnings of modern natural science will let, in my belief, the better understanding of the development of scientific writings in subsequent centuries till present days. However, the translation of the work into Polish and a wide commentary, with information on history, mission history, literature, botany, zoology, biographical notes, the interpretation of Chinese terms and also linguistic and literary theory explanations, shall become a bridge between different scientific fields, which are interested in Flora Sinensis. They might be helpful for specialists not dealing with neo-Latin (e.g. research historians, sinologists, culture experts, missions historians), for whom Latin is not a study subject nor a research tool, but who are eager to get familiar with Boym’s work and its exotic subjects. The study of the text of Flora Sinensis brings a new quality to neo-Latin works done so far. The study on Michał Boym’s works not only widens the interest of this research discipline with the text produced not in Europe, but also is an attempt to answer questions on the change of Latin in the contact with exotic cultures, on shaping a specific poetry of the neo-Latin scientific works created with the usage of the knowledge and tradition of other civilisation. They also ask about a transmission of knowledge between the East and the West, about the effects of the meeting of the civilisations and their mutual relations. From this perspective, Flora Sinensis is an important voice in the inter-civilisation dialogue, which between the West and the East has been taken since the ancient era, but sounded with a full voice only when the Jesuit missionaries arrived to China in XVI century. Through the width of their horizons, continuous desire to learn and understand “the differences” of the East Michał Boym presents himself as a true European, an envoy of an expansive and transgressive culture, which – as Zygmunt Bauman writes – “does not like the borders, as if it set them only to set the aim for its obstinate need to cross them”.
Keywords: Michał Boym SI; jezuici; Chiny w XVII wieku; chrześcijaństwo w Chinach; misje jezuickie; misjonarze; Flora Sinensis